2020
DOI: 10.1080/17482631.2020.1748942
|View full text |Cite
|
Sign up to set email alerts
|

Salutogenesis as a theoretical framework for psychosocial rehabilitation: the case of the Clubhouse model

Abstract: Purpose: This study explored whether the holistic theory of salutogenesis may be a suitable theoretical framework for the Clubhouse model of psychosocial rehabilitation, a pioneer among psychosocial rehabilitation programmes. Methods: A systematic examination of elements of the Clubhouse model, as prescribed by the Clubhouse standards, was performed within the context of the theory of salutogenesis including its basic salutogenic orientation and the main concepts of sense of coherence and resistance resources.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(119 reference statements)
1
6
0
1
Order By: Relevance
“…In line with previous studies ( 28 , 30 , 33 ), we have identified GRR in relevant vulnerable groups as a critical premise in designing mental health intervention programs. The concept of SOC can influence some psychotherapeutic modalities and psychological counseling approaches.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In line with previous studies ( 28 , 30 , 33 ), we have identified GRR in relevant vulnerable groups as a critical premise in designing mental health intervention programs. The concept of SOC can influence some psychotherapeutic modalities and psychological counseling approaches.…”
Section: Discussionsupporting
confidence: 83%
“…We expected a substantial association and prognosis of SOC both in line with burnout and in line with personal accomplishment as an aspect to mental health. The need for proactive research to identify GRR in this group is outlined ( 28 , 30 , 32 , 33 ).…”
Section: The Current Studymentioning
confidence: 99%
“…Constructs related to salutogenesis, such as measures of the SOC, have also been found to predict mental health outcomes in patients with chronic medical illnesses such as inflammatory bowel disease (Freitas et al, 2015) and cancer (Sales et al, 2014). Finally, researchers examining the effectiveness of a salutogenic approach to specific mental health problems have reported positive outcomes in child and adolescent emergency psychiatry settings (Johansson et al, 2018), and in psychosocial rehabilitation (Fekete et al, 2020).…”
Section: Salutogenic Approaches To Health Particularly Mental Healthmentioning
confidence: 99%
“…Patients with chronic mental illness often show only partial responses to standard pharmacological therapies, and rehabilitation is often essential to improving their quality of life, functioning, and social inclusion (Farkas and Anthony, 2010). In a paper describing the implementation of a comprehensive psychosocial rehabilitation program in Norway, Fekete et al (2020) have drawn on five key principles derived from the salutogenic framework: (1) health as a continuum, (2) focus on the "story" of an individual as whole rather than on a medical diagnosis, (3) GRRs, (4) the potentially adaptive aspect of tension or stress, and (5) the need for active adaptation to current circumstances. A focus on the holistic "story of a person" is of particular importance during the COVID-19 pandemic.…”
Section: Salutogenic Approaches To Health Particularly Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation